Low temperature followed by matrix solid-phase dispersion-sonication procedure for the determination of multiclass pesticides in palm oil using LC-TOF-MS - Sobhanzadeh, E.; Bakar, N.K.A.; Abas, M.R.; Nemati, K. (2011)
A simple and effective multiresidue method based on precipitation at low temperature followed by matrix solid-phase dispersion-sonication was developed and validated to determine dimethoate, malathion, carbaryl, simazine, terbuthylazine, atrazine and diuron in palm oil using liquid chromatography time-of-flight mass spectrometry (LC-TOF-MS). Liquid-liquid extraction (LLE) followed by low temperature method were optimized by studying the effect of type and volume of organic solvent (acetonitrile, acetonitrile:n-hexane (3:2 v/v) and acetone) and time of freezing to obtain high recovery yield and low co-extract fat residue in the final extract. The optimal conditions for matrix solid-phase dispersion (MSPD) were obtained using 5g of palm oil, 2g of primary secondary amine (PSA) as dispersing sorbent, 1g of graphitized carbon black (GCB) as clean-up sorbent and 15mL of acetonitrile as eluting solvent under conditions of 15min ultrasonication at room temperature. Method validation was performed in order to study sensitivity, linearity, precision, and accuracy. Average recoveries at three concentration levels (25, 50 and 100Î¼gkg-1) were found in the range of 72.6-91.3 with relative standard deviations between 5.3 and 14.2. Detection and quantification limits ranged from 1.5 to 5Î¼gkg-1and from 2.5 to 9Î¼gkg-1, respectively.